Interpretation of grave and sudden provocation in Malaysia / Mohd Safri Mohammed Na’aim - Mohammed Na’aim, Mohd Safri (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Provocation as a defence to murder is recognised under Exception 1 to section 300 of the Penal Code. One of the conditions that has to be met for a successful provocation is that the provocation must have been grave and sudden. Since murder is regarded as one of the most violent crimes, the requirements of graveness and suddenness are crucial to prevent the defence of provocation from being abused. These two requirements are cumulative, whereby if any of these elements is lacking, the defence will fail. However, a cautious reading of this Exception shows some ambiguity in the interpretation of the terms grave and sudden. This ambiguity has resulted in several interpretations by the courts. This paper aims to analyse the court’s approach towards the interpretation of these words. The paper consists of a detailed critical analysis of the Penal Code, case law and scholarly writing related to this area. The paper concludes that there still exists some ambiguity in the interpretation of grave and sudden provocation. This leaves the interpretive task solely to the court, thus resulting in a possible risk to the accused who relies on this line of defence.